2022
DOI: 10.2166/wst.2022.067
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of heavy metals by Lycium barbarum branch-based adsorbents: raw, fungal modification, and biochar

Abstract: The present study reports on the adsorptive removal of heavy metals (Cr3+, Cd2+, and Cu2+) from water by a series of Lycium barbarum branch-based adsorbents: Lycium barbarum branch (denoted as LB), fungal fermented LB (FLB), LB biochar (LBB), FLB biochar (FLBB), alkaline modified LBB (ALBB), and alkaline modified FLBB (AFLBB). The six adsorbents were characterized in terms of FTIR, SEM, surface area and pore size as well as Zeta potential. Adsorptive potential of these adsorbents was tested under varying condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…It was clear that the latter model better fitted the adsorption process in all the investigated cases (R 2 > 0.999), implying that the enzymatic hydrolysis of SCB did not alter the adsorption kinetic feature. Moreover, the results also suggested that chemical interactions occurred between SCB or SCBE and pollutants via the exchange/sharing of electrons, where strong covalent bonds were formed (Han et al, 2010;Ezeonuegbu et al, 2021;Guan et al, 2022). Furthermore, the calculated q e (cal) values and q e (exp) obtained from experiment are very similar: 24.33 vs. 24.34 mg/g for MB by SCB, 24.57 vs. 24.63 mg/g for MB by SCBE, 4.17 vs. 4.14 mg/g for Cu 2+ by SCB, and 2.59 vs. 2.58 mg/g for Cu 2+ by SCBE.…”
Section: Adsorption Of Methylene Blue Andmentioning
confidence: 88%
“…It was clear that the latter model better fitted the adsorption process in all the investigated cases (R 2 > 0.999), implying that the enzymatic hydrolysis of SCB did not alter the adsorption kinetic feature. Moreover, the results also suggested that chemical interactions occurred between SCB or SCBE and pollutants via the exchange/sharing of electrons, where strong covalent bonds were formed (Han et al, 2010;Ezeonuegbu et al, 2021;Guan et al, 2022). Furthermore, the calculated q e (cal) values and q e (exp) obtained from experiment are very similar: 24.33 vs. 24.34 mg/g for MB by SCB, 24.57 vs. 24.63 mg/g for MB by SCBE, 4.17 vs. 4.14 mg/g for Cu 2+ by SCB, and 2.59 vs. 2.58 mg/g for Cu 2+ by SCBE.…”
Section: Adsorption Of Methylene Blue Andmentioning
confidence: 88%
“…There are many heavy metal adsorption studies in the literature, especially with adsorbents obtained from natural sources such as agricultural wastes and their modified forms (Dubey & Gopal, 2007;Bansal et al, 2009;Qiao et al, 2019;Yu et al, 2022), wheat straw (Khan et al, 2021), biochar (Q. Wang et al, 2018;Guan et al, 2022), clay (Xie et al, 2018), tea plant waste (Ibrehem, 2019).…”
Section: Introductionmentioning
confidence: 99%